Continuous monoculture of Xanthoceras sorbifolia Bunge leads to continuous cropping challenges due to fungal pathogen accumulation and reduced beneficial bacteria abundance - Gongshuai Wang; Lei Wang; Mei Yu; Dan Wu; Lu Lu; Xiaoman Xie; Jinhui Lv; Yongjun Zhao (Fruit Research)
Xanthoceras sorbifolium Bunge, a unique oil crop native to northern China, has a long history of cultivation. In this study, X. sorbifolium Bunge was continuously planted in Zibo and Weifang, Shandong Province, to explore the factors that cause a decline in X. sorbifolium Bunge yield and fruit quality after long-term continuous planting. The results showed that the continuous cropping of X. sorbifolium Bunge led to a significant decrease in the biomass of the plant's seedlings, markedly reduced the root activity, and reduced the soil nutrient content. A significant change in the soil microbial community structure was observed after years of X. sorbifolia Bunge monoculture. At the genus level, the relative abundance of soil pathogenic fungi, such as Neocosmospora, Aspergillus, and Penicillium, significantly increased after continuous cropping, with the relative abundance of Neocosmospora increasing significantly in the three study sites. The abundance of common soil bacterial genera, such as Mortierella, Bacillus, and Streptomyces, is significantly lower under continuous cropping than in regular soil. The number of soil-specific bacteria was also reduced. The results showed that the accumulation of fungal pathogens, particularly Neocosmospora, may be the main challenge in the continuous cropping of X. sorbifolium Bunge, as it reduces the abundance of beneficial bacteria, primarily Bacillus, Streptomyces, and Mortierella.